Interactive Digital Media Using Canva to Enhance Students’ Literacy Skills in Integrated Mathematics–Science Learning for Fifth-Grade Students - Erna Susanti; Wasilatul Murtafiah; Lingga Nico Pradana (Postgraduate, University of Mataram, 2025)
This research and development study aimed to create Canva-based interactive digital media to enhance the mathematical literacy skills of fifth-grade students. Using the ADDIE model, the study involved two expert validators (media and materials experts with doctoral qualifications in instructional technology and more than 15 years of teaching experience) and 28 fifth-grade students from SDN Kersoharjo 2 Geneng as subjects. Expert validation used a 5-point Likert scale, yielding scores of 4.35/5.00 (87%) for materials and 4.45/5.00 (89%) for media, both categorized as highly feasible. Small-scale trials (n=10, purposive sampling) and large-scale implementation (n=28, the whole class) were conducted. Mathematical literacy was assessed through pre-test and post-test instruments covering formulation, application, interpretation, and reasoning skills. Results showed a significant improvement from the pre-test (M=62, SD=x.xx) to the post-test (M=84, SD=x.xx), with a paired t-test yielding t (27)=x.xx, p<0.05. The N-Gain score of 0.58 indicated medium effectiveness. Student response questionnaires (n=28) showed that 92% found the media attractive and that 88% reported increased confidence. The Canva-based media proved effective for enhancing mathematical literacy through interactive visual learning.